Detection of subclonal L1 transductions in colorectal cancer by long-distance inverse-PCR and Nanopore sequencing. Issue 1 (December 2017) - Pradhan, Barun; Cajuso, Tatiana; Katainen, Riku; Sulo, Päivi; Tanskanen, Tomas; Kilpivaara, Outi; Pitkänen, Esa; Aaltonen, Lauri; Kauppi, Liisa; Palin, Kimmo
Abstract Long interspersed nuclear elements-1 (L1s) are a large family of retrotransposons. Retrotransposons are repetitive sequences that are capable of autonomous mobility via a copy-and-paste mechanism. In most copy events, only the L1 sequence is inserted, however, they can also mobilize the flanking non-repetitive region by a process known as 3′ transduction. L1 insertions can contribute to genome plasticity and cause potentially tumorigenic genomic instability. However, detecting the activity of a particular source L1 and identifying new insertions stemming from it is a challenging task with current methodological approaches. We developed a long-distance inverse PCR (LDI-PCR) based approach to monitor the mobility of active L1 elements based on their 3′ transduction activity. LDI-PCR requires no prior knowledge of the insertion target region. By applying LDI-PCR in conjunction with Nanopore sequencing (Oxford Nanopore Technologies) on one L1 reported to be particularly active in human cancer genomes, we detected 14 out of 15 3′ transductions previously identified by whole genome sequencing in two different colorectal tumour samples. In addition we discovered 25 novel highly subclonal insertions. Furthermore, the long sequencing reads produced by LDI-PCR/Nanopore sequencing enabled the identification of both the 5′ and 3′ junctions and revealed detailed insertion sequence information.